Diverging trends in female old-age mortality : The United States and the Netherlands versus France and Japan - Mesle, F.; Vallin, J.
gráfs., tbls.
pp. 123-145
Keywords: Mujeres; Mortalidad; Japon; Francia; Paises Bajos; Adultos; Esperanza de Vida; Estados Unidos de America; Siglo XX